The Influence of Motivation and Competence on the Employees Performance of BPS in Pangkalpinang and South Bangka Regency - Nur Faizah; Obed Bida; Darmanto Darmanto (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This study aims to analyze the influence and competence on the employees performance of Central Statistics Agency (BPS) in Pangkalpinang City and South Bangka Regency. This type of research is quantitative research. The object of research was the employees of BPS Pangkalpinang City and BPS South Bangka Regency with total population 40 people. The analytical tools used in this research were: frequency analysis, descriptive analysis, validity test, reliability test, hypothesis testing, regression analysis, and coefficient of determination. The results of this study indicated that motivation and competence have a significant effect on the employees performance of BPS Pangkalpinang City and BPS South Bangka Regency, either partially or simultaneously. The value of the coefficient determination (R2) is 0.811, meaning that 81.1% of the employees performance of BPS Pangkalpinang City and South Bangka Regency was influenced by motivation and competence variables, while the remaining 18.9 % was influenced by other variables.